Helping Schools Plan Staff Development A Study of an Approach to In-service Education - Copeland, Willis D.; Kingsford, Steve; Far West Lab. for Educational Research and Development, San Francisco, CA. Teachers' Centers Exchange ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
The effectiveness of two approaches used by the Ventura-Santa Barbara County (California) School Resource Network to meet district-wide staff development needs is evaluated in this report. A new inservice training method, characterized by facilitation teams working within schools on site-specific needs, is contrasted to a district-wide topical workshop program already in progress. Twelve assumptions held by the network in its development of the new inservice training approach are presented and analyzed. Principal findings of the study, based on semifocused interviews, structured interviews, and questionnaires, center around: (1) the differing nature of teachers' professional needs and how identification of those needs entered into planning the facilitation team process; (2) beneficial effects of the facilitation staff development process; (3) difficulties and negative responses to the facilitated staff development process; and (4) effects of larger problems beyond the scope of the network's efforts. A summary discusses how the effects of the two approaches compare with the twelve assumptions' implicit goals. Appendixes contain a description of the methodology, examples of "shopping lists" used to assess prospective workshop participants' needs and interests, and data collection instruments. (FG)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Strategies; Educational Needs; Elementary Secondary Education; Inservice Teacher Education; Intermode Differences; Needs Assessment; Participant Satisfaction; Program Design; Program Effectiveness; Program Evaluation; School Districts; Staff Development; Teacher Attitudes; Teacher Education Programs; Teacher Workshops; Teaching Methods; Reports, Evaluative; Reports, Research